THE USEFULNESS OF MULTINOMIAL LOGIT MODELS IN EXAMINING THE RELATIONSHIP BETWEEN THE OWNERSHIP FORM OF AGRICULTURAL ENTERPRISES AND THEIR FINANCIAL-ECONOMIC RESULTS - Jabłonowski, Stanisław; Kluza, Andrzej (Metody Ilościowe w Badaniach Ekonomicznych, 2009)
From the year 1994 onwards, the magazine "Nowe ŻycieGospodarcze" has been publishing financial-economical data of the best threehundred agricultural enterprises selected from groups of such enterprises thathad chosen to participate. Makers of these lists have taken into accountenterprises which have come into being from the property of state treasury inthe nineteen nineties. The present paper takes up the problem of utilizing (toa rather limited extent) of multinomial logit models for studying the relationbetween the ownership form of agricultural enterprises and some financialeconomic characteristics, describing economic effectiveness